SARS-COV2 Source Control Conundrums: Doi: 10.36351/pjo.v37i1.1145 - Leung, Victor; Naveed, Hasan; Diab, Rawya; Liu, Christopher (Pakistan Journal of Ophthalmology, 2020)
There have been several recent publications on the exposure and control options against COVID-19.1,2 Effects of physical distancing, eye and respiratory protection and person to person spread of SARS-CoV-2 have been extensively described in literature.3 We would like to caution readers drawing causal conclusions based on statistical modelling alone for example, the beneficial effect of eye protection alone may not be biologically plausible.